Enhancing Digital Technology–Based Financial Literacy among Madrasah Students through a Community Service Program - Yuana Jatu Nilawati; Murtanto; Erliana Banjarnahor; Lailatun Hasanah; Rahma Febriana (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
This community service activity focuses on improving technology-based financial literacy among students of Madrasah Aliyah Negeri (MAN) 3 Central Jakarta. The main issue identified is the low level of students’ understanding in managing personal finances and small-scale business funds, as well as the limited use of digital financial applications in entrepreneurship learning. The purpose of this program is to provide students with practical knowledge and skills to record, plan, and control their finances effectively through digital technology. The activity was carried out using a participatory approach through counseling, training, simulation, and direct mentoring using digital financial applications such as Buku Kas and Money Lover. The results showed a significant improvement in students’ performance. In addition to enhanced knowledge, students also demonstrated more disciplined and responsible financial behavior. This program proved effective in shaping financially literate, independent, and technology-adaptive student character.